Pembelajaran Membaca Al-Quran bagi Orang Dewasa (Studi Kasus pada Kelas Talaqqi Dasar dan Talaqqi Plus di Lembaga Pendidikan Al-Quran Ash Habul Quran Kota Payakumbuh) - Dilla Ideharmida; Solfema Solfema; Irmawita Irmawita (Universitas Negeri Padang, 2018)
This research is motivated by the uniqueness of an institution that caters to the learning needs of adults through learning programs to read Al-Quran. The goal is to describe adult learning activities related to (1) learning reasons, (2) learning objectives, (3) participants 'efforts in understanding lessons, (4) institutional efforts in meeting participants learning needs, (5) learning atmosphere, (6) ) and learning methods. This research uses qualitative research method of case study type. Selection of data sources using snowball sampling technique. Data collection techniques used observation techniques, interviews, and documentation. From the research findings it is illustrated that; (1) the reason that the participants of the adults arise because of their interest and self-awareness, (2) generally each participant returns to improve the reading ability of the Quran, (3) the participants effort in understanding the lesson is to pay attention to, record and ask, organizers try to meet the learning needs of participants by providing facilities, facilities, and provide good service for participants, (5) the learning atmosphere of adult participants are different from children participants, (6) learning method used is talqin, lecture method, question and answer methods, training methods, and assignment methods.